The Implementation of Government Fixed Assets Administration: A Case Study on the Government of Aceh Singkil Regency - Hilfa Hizriati; Muhammad Arfan (Universitas Syiah Kuala, 2022)
The purpose of this study is to analyze the implementation of fixed asset administration in Aceh Singkil Government. A qualitative approach was used in this study and the sample was determined by using purposive sampling. Data source of this study is primary data. Triangulation technique was used to collect data using observation of asset administration documents, questionnaires, and in-depth interviews. The data were analyzed using qualitative analysis techniques of triangulation. In general, the results showed that the implementation of fixed asset administration in Aceh Singkil Government was still in poor criteria. This is supported by BPK's findings on the annual audit of the Aceh Singkil LKPD. Although Aceh Singkil Governmenthave obtained the WTP opinion, there are some notes on fixed assets administration that must be addressed by the Government of Aceh Singkil. Another finding is the lack of a good internal control system of fixed assets administration in the Government of Aceh Singkil. Furthermore, several factors that support and prevent the administration of fixed assets in Aceh Singkil Regency Government were found. The factors that support fixed assets administration include; an adequate understanding of the apparatus, a good ability of BMD management apparatus to operate computers, a good incentive system for BMD management apparatus, and enactment of regional regulations/qanun as the basic law to implement the government commitments of Aceh Singkil in fixing the administration of fixed assets, BPK’s routine audits, and developments in communication technology. On the other hand, factors that hinder fixed assets administration include; incomplete fixed asset data, insufficient BMD management officers in OPDs who have many fixed assets and wide distributions, human resource development opportunities for BMD management officers are still very low, and a poor internal control system. The results of this study are expected to be useful for Aceh Singkil Regency Government to improve fixed assets administration.